Podcast-Based Learning Cycle Model Learning Strategies on Creativity and Dialogue Writing Skills in High School - Vera Mustika Sari; R. Ika Mustika; Reka Yuda Mahardika (FKIP - Universitas Riau, 2026)
Learning to write dialogues is an essential competency in Indonesian language education at the senior high school level, as it develops language proficiency, creative thinking, communication skills, and the ability to organize ideas systematically. However, many students experience difficulties in generating ideas, constructing communicative conversations, and producing contextually appropriate dialogues, partly due to teacher-centered instructional approaches. This study aims to analyze the effectiveness of a podcast-based Learning Cycle instructional strategy in improving students’ creativity and dialogue-writing skills. The model integrates the Learning Cycle approach with podcast media to provide a flexible, engaging, and contextual learning experience that supports active student participation. This research employed a Research and Development (R&D) method consisting of needs analysis, model design, expert validation, implementation, and evaluation. The findings indicate that the podcast-based Learning Cycle model effectively enhances students’ creativity in generating ideas, improves their ability to construct communicative dialogues, and significantly increases learning outcomes. These results suggest that the model offers an innovative instructional alternative for fostering creativity and dialogue-writing skills while supporting technology-integrated learning in senior high school Indonesian language classrooms.